ANALISIS TINDAK TUTUR ILOKUSI FILM PENDEK “NANTI KITA CERITA TENTANG HARI INI THE SERIES EPS 01” PADA KANAL YOUTUBE TOYOTAINDONESIA - Ade Dufadhol Ariyadi; Mahatma Krishna HP; Asep Purwo Yudi Utomo (sarasvati, 2021)
AbstractToday, films have become a means of communication and conveying ideas that are increasingly massive. However, the purpose of dialogue and communication in films is sometimes not understood by most ordinary people. Therefore, we analyzed the speech act (dialogue) of one of the short films entitled "Nanti Kita Cerita Tentang Hari Ini Eps 01". The researcher has a purpose in writing this article, which is to describe, analyze, and explain the purpose of the illocutionary speech act in the short film "Nanti Kita Cerita Tentang Hari Ini Eps 01" on the toyotaindonesia youtube channel. The research method this time used descriptive qualitative, then for the technique, used the listening and note-taking technique. The results obtained in the analysis of illocutionary speech acts in the short film "Nanti Kita Cerita Tentang Hari Ini Eps 01" on the youtube channel toyotaindonesia found 9 illocutionary speech acts that have a cooperative function, 3 illocutionary acts that have a contradictory function, 2 illocutionary acts that have a function competitive, 1 illocutionary act that has a fun function. The expected results of this research will be useful for readers, especially in understanding illocutionary speech acts and can be used as teaching materials or references for learning Indonesian.Keywords: speech act analysis, illocutionary speech acts, short films, youtube